VALUE-ADDED TAX IN UZBEKISTAN: CURRENT PRACTICES, INTERNATIONAL EXPERIENCE, AND POLICY RECOMMENDATIONS FOR IMPROVEMENT (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the role and practical application of the value-added tax (VAT) in Uzbekistan, highlighting key challenges and comparing local practices with international experience. Drawing from the VAT systems of Germany, France, Turkey, and Kazakhstan, the study offers analytical insights and policy recommendations aimed at enhancing efficiency, transparency, and fairness in Uzbekistan’s VAT administration. Emphasis is placed on the reduction of bureaucratic barriers in refund procedures, the rationalization of tax exemptions, and the advancement of digital infrastructure. The article concludes with proposals to modernize VAT administration through increased automation, simplification, and digitalization, based on successful international models.